2020
DOI: 10.2174/0929866527666200525163622
|View full text |Cite
|
Sign up to set email alerts
|

Stem Bromelain Proteolytic Machinery: Study of the Effects of its Components on Fibrin (ogen) and Blood Coagulation

Abstract: Background: Antiplatelet, anticoagulant and fibrinolytic activities of stem bromelain (EC 3.4.22.4) are well described, but more studies are still required to clearly define its usefulness as an antithrombotic agent. Besides, although some effects of bromelain are linked to its proteolytic activity, few studies were performed taking into account this relationship. Objective: We aimed at comparing the effects of stem bromelain total extract (ET) and of its major proteolytic compounds on fibrinogen, fibrin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Of interest, Metzig et al [ 30 ] showed that incubation with bromelain completely prevents the thrombin-induced aggregation of platelets. Furthermore, in high doses, the enzyme complex downregulates both the external and internal pathways of the blood clotting system, inhibits fibrin synthesis and increases serum fibrinolytic activity [ 10 , 34 ]. Taken together, all these bromelain effects may contribute to the prevention of microthrombi and, thus, to the improved perfusion of the flap tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of interest, Metzig et al [ 30 ] showed that incubation with bromelain completely prevents the thrombin-induced aggregation of platelets. Furthermore, in high doses, the enzyme complex downregulates both the external and internal pathways of the blood clotting system, inhibits fibrin synthesis and increases serum fibrinolytic activity [ 10 , 34 ]. Taken together, all these bromelain effects may contribute to the prevention of microthrombi and, thus, to the improved perfusion of the flap tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In all these cases, orally administered bromelain could reduce pain and swelling and facilitate faster healing [ 6 , 8 ]. The possible mechanisms mediating these beneficial effects are the dose-dependent modulation of bradykinin secretion [ 9 ], an improved microcirculatory flow due to the fibrinolytic and anticoagulant activity of the enzymes [ 10 ], the downregulation of inflammatory mediators [ 11 ] and the modulation of leukocyte–endothelial cell interactions [ 12 ]. Interestingly, bromelain has also been shown to protect hepatocytes from apoptosis after warm ischemia [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another occasionally assumed effect traced back to the application of ED is the occurrence of (mild) coagulopathy, which is also reflected by safety notes of drug approval [63,74]. The enzyme bromelain has been associated with coagulation abnormalities in in vitro and in vivo experiments, as well as after oral medication [104][105][106][107]. A case report of Martìn et al has already drawn attention to this subject in case of topical ED using a bromelain-based approach in burn injuries [108].…”
Section: Results and Advantagesmentioning
confidence: 99%
“…Bromelain, a complex mixture of proteolytic cysteine proteases obtained from stem of pineapple (Ananas comosus) is a food supplement exhibiting a variety of pharmacological activities. Various studies substantiate the bromelain's mucolytic [13], wound healing [14], fibrinolytic [15], antiedematous [16], antithrombotic [17], anti-inflammatory [18], antioxidant [19], anticancer [20] as well as immunomodulatory activity [21]. Bromelain significantly decreases COX-2 and PGE-2 expression and lower the cytokines (IL-1β, IL-6 and TNF-α) secretion from immune cells in inflammatory conditions [22,23].…”
Section: Introductionmentioning
confidence: 94%